Abel's island - Steig, William, 1907- (New York : Farrar, Straus and Giroux, 1976)
Castaway on an uninhabited island, Abel, a very civilized mouse, finds his resourcefulness and endurance tested to the limit as he struggles to survive and return to his home.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Newbery Medal/Honor
5.5
3-6
Keywords: Mice -- Fiction; Islands -- Fiction; Survival -- Fiction; Mice -- Fiction; Survival skills -- Fiction